Best Practices for Ethical Sharing of Individual-Level Health Research Data From Low- and Middle-Income Settings. (July 2015) - Bull, Susan; Cheah, Phaik Yeong; Denny, Spencer; Jao, Irene; Marsh, Vicki; Merson, Laura; Shah More, Neena; Nhan, Le Nguyen Thanh; Osrin, David; Tangseefa, Decha; Wassenaar, Douglas; Parker, Michael
Sharing individual-level data from clinical and public health research is increasingly being seen as a core requirement for effective and efficient biomedical research. This article discusses the results of a systematic review and multisite qualitative study of key stakeholders' perspectives on best practices in ethical data sharing in low- and middle-income settings. Our research suggests that for data sharing to be effective and sustainable, multiple social and ethical requirements need to be met. An effective model of data sharing will be one in which considered judgments will need to be made about how best to achieve scientific progress, minimize risks of harm, promote fairness and reciprocity, and build and sustain trust.